Clinical significance of cytogenetic changes in childhood T-cell acute lymphoblastic leukemia: results of the multicenter group Moscow–Berlin (MB). Issue 2 (28th January 2019) - Olshanskaya, Yulia; Kazakova, Anna; Tsaur, Grigory; Zerkalenkova, Elena; Soldatkina, Olga; Aprelova, Eugenia; Plekhanova, Olga; Gindina, Tatiana; Mercur'ev, Dmitry; Barhkatov, Ildar; Baidun, Ludmila; Bydanov, Oleg; et al.
Abstract: The prognostic significance of genetic lesions in T-cell ALL still needs to be elucidated. Karyotyping and FISH were performed in samples from 120 patients with T-cell ALL registered in the trial Moscow–Berlin 2008. Most frequent rearrangements were TLX3 ( N = 29; 24%) and TAL1 ( N = 18; 15%), followed by KMT2A ( N = 6; 5%), TLX1 ( N = 5; 4.2%), and 11p13-15 ( N = 5; 4.2%). In 16.7% of patients, the karyotype was normal, and in 30.8% 'other' aberrations were seen. Patients with a normal karyotype, TAL1, or KMT2A rearrangements had the most favorable outcome (probability of event free survival (pEFS): 82% ± 6%), while prognosis for patients with TLX3 and TLX1 rearrangements and 'other' aberrations was less favorable (pEFS: 62% ± 6%). Worst outcome was observed for five patients with 11p rearrangements (pEFS: 20% ± 18%). In summary, three subgroups of patients with T-cell ALL with significantly different outcomes could be defined by cytogenetic profiling.